Counseling as a science or educational practice in multicultural philosophy dimension (A synthesize and counselor perception about counseling profession) - Zulfikar Zulfikar; Alfaiz Alfaiz; Ahmad Zaini; Septya Suarja; Nofrita Nofrita; Rici Kardo (International Journal of Research in Counseling and Education, 2019)
Counseling has been such a trend in 21 century, as a science that studied a human in psychology perspective. However, it appear with progressive touch, has affect in human mindset in every life that undertake. In 21 century development, many opinion and argumentation about counseling has an uniqueness in philosophy multicultural perspective that counseling has linkage with cultural and philosophy values in human it self, that make a new paradigm has been raise to the surface, such indigineous counseling and multicultural counseling perspective. Regardless with that paradigm, we can’t deny that basically all of science was from a human philosophy about their life with purpose to make understand and handle their life with solving a problems. But is there all of cultural and philosophy can be a such formulation to solve the problem? If cultural and philosophy values transform to such formulation as a science, is there a procedure and criteria to admitt that? Also if counseling only such philosophy or science, practical intervention, how to implemented in real life that has a multicultural and multivalues in philosophy of life? In this article, will describe such a synthesize about counseling as a  science or practical science in education in multicultural philosophy paradigm and perception counselor about counseling profession.